(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
About two-thirds of the world’s population live in rural regions and make a living via agriculture or closely related industries. This is especially true in developing nations. Food, fiber, and other agricultural byproducts are refined and distributed to customers in urban centers. Marketing in rural areas is based on four pillars: a proven product, a fair price, a convenient location, and accurate information. The core tenet of marketing is that, given the correct product, price, location, timing, and communication channel, the perfect customer will be attracted. The major goal of the research is to examine how certain obstacles affect the confidence with which entrepreneurs and small company owners in rural regions see their own chances of success. The quantitative method was used in this study, and the primary goal was to spot problems in Marketing.